"Takotsubo cardiomyopathy presenting with QT prolongation: an atypical presentation.". Issue 2 (4th March 2019) - Ali, Zain; Zain, Muhammad Abdullah; Khan, Mariya; Ahmad, Asrar; Abbas, Hassan; Ashfaq, Ammar Ali
ABSTRACT: Takotasubo Cardiomyopathy (TCM), also known as broken heart syndrome, is a syndrome of transient and reversible cardiac dysfunction in the absence of obstructive coronary artery disease following an unpleasant emotional event. TCM commonly presents as chest pain mimicking acute coronary syndrome (ACS) in character. The most common electrocardiogram (EKG) findings associated with TCM are ST-segment elevation or T wave inversion. Herein, we present a case of TCM in an individual who presented with a sudden onset chest pressure following a stressful event. She was found to have QT interval prolongation on EKG and elevated troponins. Initially thought to have non-ST elevation myocardial infarction (NSTEMI). Cardiac catheterization did not reveal coronary artery disease. The ventriculography suggested apical ballooning and the diagnosis of TCM with atypical EKG presentation. Our case is unique as we describe an atypical electrocardiographic presentation of TCM. Our case emphasizes that physicians should refrain from prescribing QT-prolonging drugs to patients with TCM, to avert potential QT prolongation and progression to torsade de pointes (TDP).